LEG EXERCISE CAN REDUCE PAIN AND IMPROVE FUNCTIONAL ACTIVITY ABILITY OF OSTEOARTHRITIS PATIENTS - Widiyono, Widiyono; Aryani, Atik; Prastikasari, Dita Ayu (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Osteoarthritis (OA) is a non-inflammatory degenerative joint disease that can affect health and tends to cause joint pain, decreased ability to function and has an impact on reducing the quality of life of sufferers. This disease most often occurs in the knee. Generally, the cause of osteoarthritis is unknown, and is called primary osteoarthritis. Efforts to reduce pain in osteoarthritis patients and improve functional activity ability are by giving leg exercise. This study aims to determine the effect of leg exercise on joint pain and functional ability of elderly people with ostheoarthritis. The research design used is a pre-experiment design using the type one group pretest-posttest design without control group. The sampling technique used purposive sampling with a total of 39 respondents. Pain assessment using Verbal Descriptor Scale (VDS) and functional ability in knee osteoarthritis (OA) patients assessed using WOMAC parameters. Data were analyzed using the Wilcoxon Signed Rank Test for joint pain data and the Paired Samples T-Test for functional ability data. The results of the Wilcoxon Signed Rank Test test obtained a p value = 0.001 (p <0.05) which means that there is an effect of leg exercise on reducing pain in osteoarthritis patients at the Mulia Hati Wonogiri General Hospital. The results of the Paired Samples T-Test Test showed a value of p = 0.001 (p <0.05), so there is an effect of leg exerrcise on improving the functional abilities of osteoarthritis patients at the Mulia Hati Wonogiri General Hospital. It is hoped that parties related to this condition can provide and provide education on leg exercise methods to reduce pain and improve the functional abilities of osteoarthritis sufferers.